Need Assessment Pengembangan Model Permainan Berbasis Outbound di Sekolah Dasar - Ardiyanto, Asep; Sukamto; Purnamasari, Veryliana; Setianingsih, Eka Sari; Azizah, Mira; Puspitasari, Nova Indah (STKIP Andi Matappa Pangkep, 2024)
Background research students who are often not enthusiastic during the learning process in class. The development of students' creative character is still not optimal, especially in 4th grade. This is because there have been no references and innovations for teachers in instilling students' character values. The aim of this research is to see to what extent this game model can improve the character of grade 4 students. The method that will be used is the research and development method.This research also uses descriptive analysis techniques. Data was taken from questionnaire responses from students, material experts and model experts. This research is the result of an outbound-based game model in the creative dimension of the Pancasila student profile to help improve students' creative character. The results of the needs assessment are in the form of interviews and observations of outbound-based game models in class 4 of SD N Karangtengah 01. The results of interviews and observations, students are often not enthusiastic during the learning process in the classroom, the development of creative character in students is still not optimal. There is no innovation and references for teachers regarding cultivating creative character in students are still less than optimal.